Validating the deuterium dilution method to measure body composition of common eider - Joshua M. Beuth; Peter W. C. Paton; Jason E. Osenkowski; Scott R. McWilliams (Wildlife Society Bulletin)
ABSTRACT We conducted the first validation of the deuterium dilution method as a nonlethal technique for estimating body composition of a sea duck. We captured male (n = 11) and female (n = 8) American common eiders (Somateria mollissima dresseri) during winters of 2011–2012 and 2012–2013 in southern New England, USA, and compared their directly measured body composition with that estimated using deuterium‐dilution. The best‐supported linear regression models predicted wet lean and fat mass with, on average, 2.0% and 20.2% relative errors, respectively. The deuterium dilution method provides field biologists and managers with a nonlethal method for accurately estimating body composition of common eider during winter. The method is broadly applicable to other migratory birds and can be used to evaluate the effects of ecological and anthropogenic drivers on body composition dynamics. © 2016 The Wildlife Society.